Artificial Intelligence Function Management in Supporting the Process of Government Implementation and Public Services in Indonesia - Saprudin, Saprudin (Journal of Management and Administration Provision, 2024)
This research investigates the impact of Artificial Intelligence (AI) on government administration and public service delivery in Indonesia.  The study employed qualitative research methods, including semi-structured interviews and detailed case studies of selected AI projects.  The research results indicate that AI has significantly improved administrative efficiency and public service delivery. The “Smart Administration System” has automated routine tasks, resulting in a 60% reduction in manual processing times and enhancing overall productivity. The “Policy Insight Tool” has supported better policy formulation through advanced predictive analytics and scenario modeling. Despite these successes, the study identified challenges such as resistance to change, technical difficulties, and data integration issues. Feedback from users also highlighted limitations in AI language processing and accessibility concerns.